High prevalence of human papillomavirus type 58 in HIV infected men who have sex with men: A preliminary report in Central Italy. Issue 5 (28th October 2015) - Sammarco, Michela Lucia; Ucciferri, Claudio; Tamburro, Manuela; Falasca, Katia; Ripabelli, Giancarlo; Vecchiet, Jacopo
Abstract : Human papillomavirus (HPV) infection and type‐specific prevalence at anal, oral, coronal sulcus, and urethral mucosa in fifty HIV positive men having sex with men (MSM) were evaluated; patients were enrolled in a non‐metropolitan area of Central Italy. Clinical and socio‐demographic information, drug, and sexual behaviors were obtained for each participant. HPV was detected by PCR from an overall of 200 specimens, and genotyping was performed by both Restriction Fragment Length Polymorphism analysis and sequencing. HPV DNA was found in 60.0% (n = 30) of HIV positive MSM, and prevalence was higher at anal canal (n = 28, 56.0%) compared to all the other anatomical sites (χ 2 test P  < 0.01) of coronal sulcus (n = 11, 22.0%), oral (n = 8, 16.0%), and urethral mucosa (n = 5, 10.0%). We found 63.3% (n = 19) of MSM with at least one high‐risk genotype, and HPV‐58 was more frequently detected (n = 9, 47.4%) respect to HPV‐16 (n = 6, 31.6%). This is the first report on HPV detected at four anatomical sites involved in sexual practices in HIV positive MSM. We found an unusual distribution of oncogenic genotypes with an exceeding prevalence of HPV‐58 respect to HPV‐16. Hence, the recently licensed nonavalent vaccine should be suitable to prevent a larger number of infections caused by potentially emerging high‐risk genotypes. J. Med. Virol. 88:911–914, 2016 . © 2015 Wiley Periodicals, Inc.